Urban justice - Seagal, Steven; Griffin, Eddie, 1968-; Trejo, Danny, 1944-; Woller, Kirk B. R.; Yorker, Jade.; Serrano, Carman; Carstens, Liezl; Evans, Mary.; Sony Pictures Home Entertainment; XIT Financial Group; Steamroller (Firm) ([United States] : Sony Pictures Home Entertainment, 2007)
Simon has a dark and violent past, and now is bent on revenge after his son is murdered.
Music by Peter Meisner ; edited by Scott Conrad ; director of photography, Don E. Fauntleroy.
Steven Seagal, Eddie Griffin, Danny Trejo, Kirk B.R. Woller, Jade Yorker, Carman Serrano, Liezl Carstens, Mary Evans.
Rating: R; strong violence; pervasive language; and some drug content.
DVD ; Dolby digital ; mastered in high definition.
English, French, Portuguese, Spanish or Thai dialogue; French, Korean, Mandarin, Portuguese, Spanish or Thai subtitles.
Closed-captioned.
Keywords: Videorecordings for the hearing impaired; Police -- Drama; Homicide -- Drama; Fathers -- Drama; Feature films; Adventure films; Gangster films; Video recordings for the hearing impaired; Adventure -- Feature; Gangster -- Feature